School Community Empowerment Program for Conservation of Riparian Vegetation around the Bedog River in Godean, Sleman - Abdul Razaq Chasani; Siti Aisah; Hayinnatus Sholihah; Handasari Mokodompit (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Due to the increasingly intensive interaction between humans and the river, the riparian vegetation conservation program was implemented to keep the Bedog River sustainable. This program aims to provide awareness and a good understanding of the dynamic balance between human life and the river environment, especially the conservation of riparian vegetation as a river key system that can be done. To achieve these aims, three approaches were implemented, i.e.: 1) empowering SMPIT Alam Nurul Islam Yogyakarta as a pioneer of the school community concern in the conservation of riparian vegetation by forming a